2012
DOI: 10.1038/bmt.2012.145
|View full text |Cite
|
Sign up to set email alerts
|

Pegfilgrastim compared with filgrastim for cytokine-alone mobilization of autologous haematopoietic stem and progenitor cells

Abstract: Haematopoietic stem and progenitor cells (HSPC) mobilization, using cytokine-alone, is a well-tolerated regimen with predictable mobilization kinetics. Single-dose pegfilgrastim mobilizes HSPC efficiently; however, there is surprisingly little comparative data on its use without chemotherapy for HSPC mobilization. Pegfilgrastim-alone and filgrastim-alone mobilization regimens were compared in 52 patients with haematological malignancy. Pegfilgrastim 12 mg (n ¼ 20) or 6 mg (n ¼ 2) was administered Day 1 (D1) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…No advantage has been shown by split dosing G-CSF [45,46]. There is emerging data on the efficacy of 12 mg pegfilgrastim as a single subcutaneous dose [47]. However, pegfilgrastim has not been adopted by many centers, likely because of ease and familiarity of use with G-CSF and cost.…”
Section: Question 5: What Type Of Venous Access Is Recommended?mentioning
confidence: 99%
“…No advantage has been shown by split dosing G-CSF [45,46]. There is emerging data on the efficacy of 12 mg pegfilgrastim as a single subcutaneous dose [47]. However, pegfilgrastim has not been adopted by many centers, likely because of ease and familiarity of use with G-CSF and cost.…”
Section: Question 5: What Type Of Venous Access Is Recommended?mentioning
confidence: 99%
“…There was a theoretical concern regarding the risk of hyperleukocytosis with pegfilgrastim plus plerixafor, which was not borne out in this study. One historical control patient mobilized with pegfilgrastim alone at our institution 20 had developed hyperleukocytosis after a dose of pegfilgrastim 12 mg for the purposes of cytokine-alone mobilization. Although this case resolved without incident, a dose of pegfilgrastim 6 mg was chosen prospectively for this study and no cases of hyperleukocytosis were observed.…”
Section: P-valuementioning
confidence: 99%
“…[68][69][70] A single dose of pegfilgrastim also may be used for mobilization; although extensively used elsewhere, it has not been adopted by our group. 71 BLOOD…”
mentioning
confidence: 99%